Structural Change: Industry’s Fear of the Future - Marten von Werder; Ralf Rukwid (Wirtschaftsdienst)
Abstract The coronavirus crisis obscures the extent to which structural change leads to widespread job losses in the German industrial sector. However, not all structural change is the same: the choice of policy approaches with which digitalisation and decarbonisation are implemented has significant influence on how the prospects for employees in this sector develop. Small businesses in particular seem to be at risk, regardless of their profitability, because the framework conditions for transformation are too uncertain. A comprehensive employee survey shows that there is great uncertainty in the leading sectors of the German industry. In many places, employees fear for their jobs and hope for more on-the-job training and a targeted, active industrial policy — this is a challenge for the next federal government.